Polimorfismos de nucleotídeo único BsmI e TaqI no gene do VDR e excesso de peso gestacional - Fernandes, Karla Gabrielle Sales (2023)
Introduction: Excessive gestational weight is related to an increased risk of adverse perinatal complications and metabolic diseases. Added to factors inherent to pregnancy and the environment, 20% of the variability in gestational weight gain can be explained by genetic variants. Among the genetic alterations commonly studied in the Brazilian population, the single nucleotide polymorphisms (Single Nucleotide Polymorphism - SNPs) BsmI and TaqI, present in the Vitamin D Receptor (VDR), stand out. Objective: To investigate the relationship between the SNP BsmI (rs1544410) and TaqI (rs731236) of the VDR gene with excess gestational weight. Methods: Cross-sectional study carried out with 121 pregnant women over 18 years of age, in different gestational trimesters, assisted by the public health network in the city of Aracaju, Sergipe. Sociodemographic, economic and obstetric information were obtained through interviews with the application of semi-structured questionnaires, and anthropometric data were collected from the records in the pregnant woman's book. The concentrations of 25- hydroxyvitamin D [25(OH)D] were analyzed by the chemiluminescence method and for SNPs genotyping we used the TaqMan system. Gestational excess weight was assessed by weekly weight gain (WG) and gestational BMI. Participants were classified according to weekly weight gain (WG) and gestational BMI into excessive and non-excessive. Vitamin D status was classified into insufficiency/deficiency and sufficiency. SNP genotypes were classified as: SNP BsmI: B/B (reference genotype), B/b (heterozygous genotype) and b/b (polymorphic); SNP TaqI: T/T (reference genotype), T/t (heterozygous genotype) and t/t (polymorphic), the genotypes were further classified into dominant (BsmI: BB vs bb + Bb; TaqI: TT vs tt + Tt) and recessive (BsmI: BB + Bb vs bb; TaqI: TT + Tt vs tt) groups. For statistical analysis, chisquare and logistic multivariate regression models were performed to assess differences in genotype distribution and associations with excessive weekly WG and overweight gestational BMI. Data were controlled for confounding variables. Results: The frequencies of recessive SNPs BsmI and TaqI genotypes were 21.5% and 6.6%, respectively. The frequencies of reference genotypes were 28.9% for SNP BsmI and 43.8% for TaqI, and of heterozygous genotype 49.6% for both SNPs. No associations were found between the polymorphic b alleles of the BsmI SNP with excessive weight gain (p= 0.100) and with excess gestational weight (p= 0.451). There were also no associations between the polymorphic t allele of the TaqI SNP with excessive weight gain (p= 0.578) and excess gestational weight (p= 0.352). There were no significant differences between the bb genotypes of the SNPs BsmI with the categories of excessive weight gain (p= 0.084) and excess gestational weight (p= 0.887); no association was found between the tt genotype of the SNP TaqI with the categories of excessive weight gain (p= 0.955) and excess gestational weight (p= 0.072). No significant differences were found between vitamin D nutritional status with excessive gestational WG and gestational BMI and with BsmI and TaqI genotypes (p > 0.05). Conclusion: Our findings indicate that there is no association between the allele frequency, genotype, dominant and recessive models, of the BsmI and TaqI SNPs with excess gestational weight.